Micro, Small and Medium Enterprise Finance in India : A Research Study on Needs, Gaps and Way Forward - International Finance Corporation (International Finance Corporation, New Delhi, 2017)
This study aims to provide an assessment of the Micro, Small and Medium Enterprise sector (MSME) finance in India. The chapters in the study highlight the key characteristics of the MSME sector, and assess the demand for, and the flow of finance into the sector. The study also evaluates the consequent gap in the financing needs of MSMEs. Finally, it explores potential interventions to address the lack of access to formal finance for MSMEs. The Micro, Small and Medium Enterprise sector is crucial to India’s economy. There are 29.8 million enterprises in various industries, employing 69 million people. The sector includes 2.2 million women-led enterprises (~7.4 percent) and ~15.4 million rural enterprises (51.8 percent). In all, the MSME sector accounts for 45 percent of Indian industrial output and 40 percent of exports. Although 94 percent of MSMEs are unregistered, the contribution of the sector to India’s GDP has been growing consistently at 11.5 percent a year, which is higher than the overall GDP growth of 8 percent. Poor infrastructure and inadequate market linkages are key factors that have constrained growth of the sector. The lack of adequate and timely access to finance has been the biggest challenge. The financing needs of the sector depend on the size of operation, industry, customer segment, and stage of development. Financial institutions have limited their exposure to the sector due to a higher risk perception and limited access of MSMEs to immovable collateral.